Negative electrode sheet, method for manufacturing the same, and battery
Patent Information
- Application Number
- CN202510819544.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-17
AI Technical Summary
[0005]有鉴于此,本发明致力于提供一种负极片及其制备方法和电池,以解决现有技术中负极片无法兼顾快充性能和循环性能的问题
本发明的负极材料通过进行结构化分层设计,利用不同材料的相互协同作用,以及进一步通过表面改性等方式提高电池能量密度和快充能力,改善高低温性能和涂层之间的界面结合等问题。第一层包括石墨负极,具有循环稳定性好,首效高的特点;第二层包括硅基负极材料,具有较高的容量,能够提高电池的能量密度,且较高的嵌锂电位能够减少锂的析出;第三层包括导热导电性能以及具有一定的弯曲强度和抗拉强度的Mxene锂离子电池负极材料,能够缓解硅的体积膨胀,并且硅也能够补足Mxene的克容量相对较低的问题,并且Mxene本身就具备极佳的导电性,使得远离集流体一侧具有较好的离子和电子电导率。
Smart Images

Figure CN120709291B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, specifically to a negative electrode sheet, its preparation method, and a battery. Background Technology
[0002] In recent years, as lithium-ion batteries have matured, their application scope and demand have gradually increased. Higher performance requirements are placed on lithium-ion batteries, demanding not only high energy density but also fast charging capabilities. This is typically achieved by increasing electrode thickness and the proportion of active material. However, thicker electrodes also bring a series of problems. The significant difference in ionic and electronic conductivity between the inner and outer sides of the electrode, due to its deviation from the current collector, leads to pronounced electrochemical polarization. Furthermore, the electrolyte lacks good wetting properties on the inner electrode, failing to form a proper channel. This results in poor battery capacity utilization, low rate performance, high temperature rise, and a tendency for lithium plating. Therefore, researching and exploring high-energy-density and long-cycle-life anode materials is a pressing issue for lithium-ion batteries.
[0003] Thick electrodes can be classified into single-layer, double-layer, triple-layer, and multi-layer types based on the number of layers. Single-layer thick coatings cannot improve energy density or address the significant differences between the outer and inner layers. Double-layer thick coatings mostly use a mixture of artificial and natural graphite particles for thick electrode design, but their energy density is lower compared to silicon-carbon or silicon-oxygen systems. They are suitable for silicon-carbon systems, but they cannot solve the problem of low conductivity and cannot suppress the large volume expansion rate during charge and discharge.
[0004] Therefore, when designing electrode structures by utilizing the characteristics of various negative electrode materials to meet battery performance indicators, it is crucial to ensure the compatibility of the interfaces between coatings. Summary of the Invention
[0005] In view of this, the present invention aims to provide a negative electrode sheet, its preparation method and battery, to solve the problem that the negative electrode sheet in the prior art cannot simultaneously achieve fast charging performance and cycle performance.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: The present invention provides a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector, a first negative electrode active layer disposed on at least one side surface of the negative electrode current collector along the thickness direction, a second negative electrode active layer disposed on one side surface of the first negative electrode active layer away from the negative electrode current collector, and a third negative electrode active layer disposed on one side surface of the second negative electrode active layer away from the first negative electrode active layer. The first negative electrode active layer includes a first negative electrode active material, which includes a modified graphite material; the modified graphite material includes graphite and a first coating layer covering the surface of the graphite, the first coating layer including a conductive material modified with carboxyl or hydroxyl groups; The second negative electrode active layer includes a second negative electrode active material, which includes a modified silicon-based material; the modified silicon-based material includes a silicon-based material and a second coating layer covering the surface of the silicon-based material, the second coating layer including a carbon material and a cationic polymer; The third negative electrode active layer includes a third negative electrode active material, which includes a modified MXene material. The modified MXene material includes an MXene material and a third coating layer covering the surface of the MXene material. The third coating layer includes a conductive material modified with carboxyl or hydroxyl groups.
[0007] Optionally, the areal density ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer is (1~3):(1~3):(1~3); optionally, the areal density of the first negative electrode active layer is 0.01~0.12 g / cm³. 2 Optionally, the areal density of the second negative electrode active layer is 0.01~0.12 g / cm³. 2 Optionally, the areal density of the third negative electrode active layer is 0.01~0.12 g / cm³. 2 .
[0008] Optionally, the thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer is (1.25~3.35):(1~2):(1~2); Optionally, the thickness of the first negative electrode active layer is 0.044~0.067mm; Optionally, the thickness of the second negative electrode active layer is 0.02~0.040mm; Optionally, the thickness of the third negative electrode active layer is 0.02~0.040mm.
[0009] Optionally, the mass ratio of the graphite to the conductive material modified with carboxyl or hydroxyl groups is (94~99):(1~6); Optionally, the thickness of the first coating layer is 20~80 nm; Optionally, the conductive material modified with carboxyl or hydroxyl groups in the modified graphite material includes graphene oxide.
[0010] Optionally, the mass ratio of the silicon-based material, the carbon material, and the cationic polymer is (84~97):(2~16):(1~10); Optionally, the thickness of the second coating layer is 10~50 nm; Optionally, the silicon-based material includes at least one of silicon-carbon material, silicon-oxygen material, and nano-silicon; Optionally, the silicon-oxygen material includes SiO2. xWherein, 0.5 ≤ x ≤ 1.5 and / or x = 2; optionally, the carbon material includes one-dimensional carbon material or two-dimensional carbon material; or, the carbon material includes zero-dimensional carbon material, and at least one of one-dimensional carbon material and two-dimensional carbon material; optionally, the zero-dimensional carbon material includes graphite particles and / or conductive carbon black; optionally, the one-dimensional carbon material includes carbon nanotubes and / or carbon fibers; optionally, the two-dimensional carbon material includes graphene and / or graphene oxide; optionally, the cationic polymer includes polydiallyldimethylammonium chloride.
[0011] Optionally, the mass ratio of the MXene material to the carboxyl- or hydroxyl-modified conductive material is (90~99):(1~10); optionally, the thickness of the third coating layer is 20nm~200nm; optionally, the MXene material includes Ti3C2T. x Optionally, the modified MXene material may contain carboxyl or hydroxyl-modified conductive materials, including graphene oxide.
[0012] Optionally, the first negative electrode active layer further includes a first binder, a first dispersant, and a first conductive agent; optionally, the mass ratio of the first negative electrode active material, the first binder, the first dispersant, and the first conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1); optionally, the second negative electrode active layer further includes a second binder, a second dispersant, and a second conductive agent; optionally, the mass ratio of the second negative electrode active material, the second binder, the second dispersant, and the second conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1); optionally, the third negative electrode active layer further includes a third binder, a third dispersant, and a third conductive agent; optionally, the mass ratio of the third negative electrode active material, the third binder, the third dispersant, and the third conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1).
[0013] Optionally, the first, second, and third adhesives each independently include at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polyacrylate, polyimide, polyamide, polyvinyl alcohol, and polytetrafluoroethylene; optionally, the first, second, and third dispersants each independently include at least one of carboxymethyl cellulose, sodium dodecylbenzene sulfonate, and polyvinylpyrrolidone; optionally, the first, second, and third conductive agents each independently include at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon fibers, and graphene.
[0014] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps: S1. A first negative electrode active slurry is coated onto at least one side surface of the current collector along the thickness direction to form a first negative electrode active layer on the current collector. S2. The second negative electrode active slurry is coated on the surface of the first negative electrode active layer away from the current collector to form the second negative electrode active layer on the first negative electrode active layer. S3. Coat the third negative electrode active slurry onto the surface of the second negative electrode active layer away from the first negative electrode active layer to form the third negative electrode active layer on the second negative electrode active layer. The first negative electrode active slurry includes modified graphite material; The second negative electrode active slurry includes modified silicon-based materials; The third negative electrode active slurry includes modified MXene material.
[0015] A third aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode comprises the negative electrode described above or a negative electrode prepared according to the preparation method described above.
[0016] The beneficial technical effects of the present invention through the above technical solution are as follows: The anode material of this invention utilizes a structured, layered design, leveraging the synergistic effects of different materials and further improving battery energy density and fast-charging capability through surface modification, while also addressing issues such as high and low temperature performance and interfacial bonding between coatings. The first layer comprises a graphite anode, characterized by good cycle stability and high initial efficiency. The second layer comprises a silicon-based anode material, exhibiting high capacity, enhancing battery energy density, and its high lithium intercalation potential reduces lithium deposition. The third layer comprises Mxene lithium-ion battery anode material with excellent thermal and electrical conductivity, as well as certain flexural and tensile strength. This mitigates silicon volume expansion, and silicon also compensates for the relatively low specific capacity of Mxene. Furthermore, Mxene itself possesses excellent conductivity, resulting in good ionic and electronic conductivity on the side furthest from the current collector.
[0017] This invention improves interface and overall kinetic issues by surface modification of each material layer. It maximizes the ion diffusion capabilities of each material layer. By designing a stacked structure of anode materials with different physical and electrochemical properties, it enhances the overall performance of the anode material in terms of adhesion, internal structure, diffusion channels, and safety. The three-layer coating structure of the lithium-ion battery anode material in this invention improves the energy density, cycle life, and fast charging performance of lithium-ion batteries through the synergistic effect of different active anode materials. It achieves a balance between high specific capacity and kinetic performance, exhibits excellent low-temperature charging capability, and is beneficial for increasing the capacity of lithium-ion batteries and enabling fast charging.
[0018] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0019] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0020] Figure 1 The diagram shown is a schematic diagram of the negative electrode sheet of the present invention.
[0021] Figure 2 The diagram shows the interface between the first negative electrode active layer and the second negative electrode active layer in the negative electrode sheet of the present invention.
[0022] Explanation of reference numerals in the attached figures: 10-Negative electrode current collector; 20-First negative electrode active layer; 30-Second negative electrode active layer; 40-Third negative electrode active layer; 50-Conductive material modified with carboxyl or hydroxyl groups; 60-Catonic polymer; 70-Silicon-based material; 80-Carbon material. Detailed Implementation
[0023] This invention discloses a negative electrode sheet, its preparation method, and a battery. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired result. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
[0024] In the description of this invention, the list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0027] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0029] To address the issue that existing negative electrode sheets cannot simultaneously achieve fast charging performance and cycle performance, this invention adopts the following technical solution: refer to Figure 1 As shown, the present invention provides a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector 10, a first negative electrode active layer 20 disposed on at least one side surface of the negative electrode current collector along the thickness direction, a second negative electrode active layer 30 disposed on one side surface of the first negative electrode active layer away from the negative electrode current collector, and a third negative electrode active layer 40 disposed on one side surface of the second negative electrode active layer away from the first negative electrode active layer. The first negative electrode active layer 20 includes a first negative electrode active material, which includes a modified graphite material; the modified graphite material includes graphite and a first coating layer covering the surface of the graphite, the first coating layer including a conductive material modified with carboxyl or hydroxyl groups. The second negative electrode active layer 30 includes a second negative electrode active material, which includes a modified silicon-based material; the modified silicon-based material includes a silicon-based material and a second coating layer covering the surface of the silicon-based material, the second coating layer including a carbon material and a cationic polymer; The third negative electrode active layer 40 includes a third negative electrode active material, which includes a modified MXene material. The modified MXene material includes an MXene material and a third coating layer covering the surface of the MXene material. The third coating layer includes a conductive material modified with carboxyl or hydroxyl groups.
[0030] In this application, the provided negative electrode sheet includes a negative electrode current collector 10, a first negative electrode active layer 20 with modified graphite material coated with carbon material as the active material, a second negative electrode active layer 30 with modified silicon-based material as the active material, and a third negative electrode active layer 40 with modified MXene material as the active material, which are designed to be stacked in sequence. That is, the negative electrode materials with different properties are combined to improve the energy density and fast charging capability of the negative electrode sheet by utilizing the synergistic effect of different materials and further modifying the surface of graphite, silicon-based material and MXene material, and improving high and low temperature performance and interfacial bonding between coatings.
[0031] In this invention, the first layer comprises graphite material with small volume change and long cycle life, which meets the requirements for good use of the battery under high current charge and discharge. The graphite material is coated with a conductive material modified with carboxyl or hydroxyl groups. The conductive material modified with carboxyl or hydroxyl groups has excellent conductivity, which can improve the kinetic performance of the first layer material. The second layer comprises silicon-based material coated with carbon material and cationic polymer. The silicon-based material is in the middle layer, which can improve the overall lithium intercalation potential of the negative electrode material. Compared with a single graphite layer, it can ensure that lithium plating phenomenon is reduced and the safety performance is high. Moreover, the silicon-based material has a high capacity, which allows for sufficient lithium intercalation and helps to realize the specific capacity. Silicon-based materials experience significant volume expansion during charging and discharging. Placing them in the middle layer, the expansion is suppressed due to the constraint of the upper and lower layers. The high elasticity and strength of carbon materials effectively bind the material particles during the volume expansion of silicon-based materials, reducing the shedding of active material, improving the structural stability of the anode material, and compensating for the poor conductivity of silicon-carbon materials. Simultaneously, the cationic polymer allows the negatively charged materials on the surfaces of the first and third layers to bond with the positively charged materials on the surface of the second layer due to electrostatic attraction, thereby improving the compatibility and tightness of the interfaces. A schematic diagram of the interface between the first and second anode active layers is shown below. Figure 2As shown; the third layer includes Mxene material. Although Mxene material has a lower capacity, this disadvantage is compensated by the silicon-based material in the middle layer. Mxene material has high tensile strength and high flexural strength, and can absorb the expansion of the middle silicon layer. The introduction of conductive materials modified with carboxyl or hydroxyl groups also solves the problem of MXene self-stacking, increases the interlayer spacing, and its good lithium-ion diffusion channels can improve the high-current charge-discharge performance and low-temperature performance of the battery, meeting the power performance requirements. At the same time, the high stability of hard carbon in the electrolyte can effectively reduce the occurrence of electrolyte side reactions. In addition, Mxene has excellent conductivity, which can improve the kinetics of the outer layer. In general, by designing the anode material in a structured layered manner, the compaction density of the layered composite anode can be improved, avoiding structural damage to the anode material and maximizing the ion diffusion capacity of each layer of material. By designing the stacked structure of anode materials with different physical and electrochemical properties, the adhesion ability, internal structure, and diffusion channels of the composite anode can be effectively improved, enhancing the overall performance of the anode material and promoting the good parallel development of energy density and power characteristics of lithium-ion batteries.
[0032] The negative electrode sheet of this invention has a three-layer coating structure. Through the synergistic effect of different negative electrode active materials, it improves the energy density performance, long cycle life performance, and fast charging performance of lithium-ion batteries, achieving a balance between high specific capacity and dynamic performance. It also has better low-temperature charging capability and is a promising three-layer coating structure for lithium-ion batteries to achieve high-capacity fast charging. Through reasonable layer matching and control, it improves the problem of poor interface compatibility between layers while ensuring high energy density and fast charging capability.
[0033] According to the present invention, the areal density ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer can be (1~3):(1~3):(1~3). In the present invention, a suitable areal density ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer helps to balance performance such as capacity, interface, and kinetics. As an example, the areal density ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer can be any value among 1:1:1, 1:1:2, 1:1:3, 1:2:1, 1:2:2, 1:2:3, 2:1:3, 2:2:3, 3:1:1, and 3:2:1, or any value within the range of any pair of the above values. In this invention, if the areal density ratio of the first negative electrode active layer, the second negative electrode active layer and the third negative electrode active layer is too large, it will lead to insufficient power performance and poor interface stability, thereby affecting the fast charging capability; if the areal density ratio of the first negative electrode active layer, the second negative electrode active layer and the third negative electrode active layer is too small, it will lead to a lower specific capacity.
[0034] According to the present invention, the areal density of the first negative electrode active layer can be 0.01~0.12 g / cm³. 2 In this invention, a suitable areal density of the first negative electrode active layer helps to ensure a certain fast charging capability. As an example, the areal density of the first negative electrode active layer can be 0.01 g / cm³. 2 0.02g / cm 2 0.04g / cm 2 0.05g / cm 2 0.06g / cm 2 0.08g / cm 2 0.1g / cm 2 and 0.12g / cm 2 Any value in the range or any value within the range formed by any two of the above values. In this invention, if the areal density of the first negative electrode active layer is too large, the capacity of the composite electrode will be insufficient; if the areal density of the first negative electrode active layer is too small, the kinetic performance will be poor.
[0035] According to the present invention, the areal density of the second negative electrode active layer can be 0.01~0.12 g / cm³. 2 In this invention, a suitable areal density of the second negative electrode active layer helps to improve the overall capacity. As an example, the areal density of the second negative electrode active layer can be 0.01 g / cm³. 2 0.02g / cm 2 0.04g / cm 2 0.05g / cm 2 0.06g / cm 2 0.08g / cm 2 0.1g / cm 2 and 0.12g / cm 2 Any value in the range or any value within the range formed by any two of the above values. In this invention, if the areal density of the second negative electrode active layer is too large, it will result in a large expansion coefficient and poor interface stability; if the areal density of the second negative electrode active layer is too small, it will result in insufficient capacity utilization.
[0036] According to the present invention, the areal density of the third negative electrode active layer can be 0.01~0.12 g / cm³. 2 In this invention, a suitable areal density of the third negative electrode active layer helps to form a good conductive network, thereby improving the overall kinetics. As an example, the areal density of the third negative electrode active layer can be 0.01 g / cm³. 2 0.02g / cm 2 0.04g / cm 2 0.05g / cm 2 0.06g / cm2 0.08g / cm 2 0.1g / cm 2 and 0.12g / cm 2 Any value in the range or any value within the range formed by any two of the above values. In this invention, if the areal density of the third negative electrode active layer is too large, it will lead to an uneven structure in the formation of the conductive network, affecting the fast charging capability; if the areal density of the third negative electrode active layer is too small, it will lead to insufficient capacity and kinetics.
[0037] According to the present invention, the compaction density of the first negative electrode active layer can be 1.2~1.8 g / cc. In the present invention, a suitable compaction density of the first negative electrode active layer helps to balance the overall capacity and ensure a certain porosity structure. As an example, the compaction density of the first negative electrode active layer can be any value among 1.2 g / cc, 1.3 g / cc, 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, and 1.8 g / cc, or any value within the range formed by any two of the above values. In the present invention, if the compaction density of the first negative electrode active layer is too high, it will lead to obstruction of ion transport distance; if the compaction density of the first negative electrode active layer is too low, it will lead to low overall capacity utilization.
[0038] According to the present invention, the compaction density of the second negative electrode active layer can be 1.2~1.8 g / cc. In the present invention, a suitable compaction density of the second negative electrode active layer helps to improve the overall energy density and ensure a certain crystal structure. As an example, the compaction density of the second negative electrode active layer can be any value among 1.2 g / cc, 1.3 g / cc, 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, and 1.8 g / cc, or any value within the range formed by any two of the above values. In the present invention, if the compaction density of the second negative electrode active layer is too high, it may lead to particle breakage and crystal structure failure; if the compaction density of the second negative electrode active layer is too low, it will lead to a large coefficient of expansion, thereby affecting cycle performance.
[0039] According to the present invention, the compaction density of the third negative electrode active layer can be 1.2~1.8 g / cc. In the present invention, a suitable compaction density of the third negative electrode active layer helps to improve the conductive network structure. As an example, the compaction density of the third negative electrode active layer can be any value selected from 1.2 g / cc, 1.3 g / cc, 1.4 g / cc, 1.5 g / cc, 1.6 g / cc, 1.7 g / cc, and 1.8 g / cc, or any value within the range formed by any two of the above values. In the present invention, if the compaction density of the third negative electrode active layer is too high, it will affect the fast charging capability; if the compaction density of the third negative electrode active layer is too low, it will lead to an increase in the rebound rate after cycling and insufficient capacity utilization.
[0040] According to the present invention, the thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer can be (1.25~3.35):(1~2):(1~2). In the present invention, a suitable thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer helps to ensure fast charging capability, capacity utilization, and the construction of the conductive network. As an example, the thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer can be any value among 1.25:1:1, 1.25:1:2, 1.5:2:2, 2:1:1, 2:2:1, 2.5:1:1, 2.5:2:1, 3:1:1, 3:2:1, 3.35:1:2, and 3.35:2:1, or any value within the range of any pair of the above values. In this invention, if the thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer is too large, it will result in insufficient fast charging capability; if the thickness ratio of the first negative electrode active layer, the second negative electrode active layer, and the third negative electrode active layer is too small, it will result in insufficient capacity utilization.
[0041] According to the present invention, the thickness of the first negative electrode active layer can be 0.044~0.067 mm. In the present invention, a suitable thickness of the first negative electrode active layer helps to balance fast charging capability and capacity. As an example, the thickness of the first negative electrode active layer can be any value among 0.044 mm, 0.045 mm, 0.05 mm, 0.055 mm, 0.06 mm, 0.065 mm, and 0.067 mm, or any value within the range formed by any two of the above values. In the present invention, if the thickness of the first negative electrode active layer is too thick, it will increase the ion transport path and affect the kinetic performance; if the thickness of the first negative electrode active layer is too thin, it will be unable to suppress the changes in silicon-based rebound, thereby causing interface failure.
[0042] According to the present invention, the thickness of the second negative electrode active layer can be 0.02~0.040 mm. In the present invention, a suitable thickness of the second negative electrode active layer helps to improve capacity utilization. As an example, the thickness of the second negative electrode active layer can be any value selected from 0.02 mm, 0.025 mm, 0.03 mm, 0.035 mm, and 0.04 mm, or any value within the range formed by any two of the above values. In the present invention, if the thickness of the second negative electrode active layer is too thick, it will lead to a large electrode cycle rebound rate and capacity loss; if the thickness of the second negative electrode active layer is too thin, it will lead to an insignificant increase in capacity.
[0043] According to the present invention, the thickness of the third negative electrode active layer can be 0.02~0.040 mm. In the present invention, a suitable thickness of the third negative electrode active layer helps to suppress the expansion changes of the second layer and construct a suitable conductive network. As an example, the thickness of the third negative electrode active layer can be any value among 0.02 mm, 0.025 mm, 0.03 mm, 0.035 mm, and 0.04 mm, or any value within the range formed by any two of the above values. In the present invention, if the thickness of the third negative electrode active layer is too thick, it will affect the electrolyte wetting effect and the fast charging capability; if the thickness of the third negative electrode active layer is too thin, it will lead to an unstable interface between the second and third layers and result in an uneven formation of the kinetic network.
[0044] According to the present invention, the mass ratio of graphite to the carboxyl- or hydroxyl-modified conductive material can be (94~99):(1~6). In this invention, a suitable mass ratio of graphite to the carboxyl- or hydroxyl-modified conductive material helps to form a uniform coating layer. As an example, the mass ratio of graphite to the carboxyl- or hydroxyl-modified conductive material can be any value from 94:6, 95:5, 96:4, 97:3, 98:2, 99:1, 99:2, 99:3, and 99:6, or any value within the range of any pair of the above values. In this invention, if the mass ratio of graphite to the carboxyl- or hydroxyl-modified conductive material is too large, it will lead to insufficient kinetic performance or uneven coating; if the mass ratio is too small, it will result in reduced capacity utilization and lower first-time efficiency.
[0045] According to the present invention, the thickness of the first coating layer can be 20-80 nm. In this invention, a suitable thickness of the first coating layer helps to not only improve the fast-charging performance of the first layer itself, but also to integrate with other interfaces, resulting in a good conductive network for the new vehicle. As an example, the thickness of the first coating layer can be any value selected from 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, and 80 nm, or any value within the range formed by any pair of the above values. In this invention, if the thickness of the first coating layer is too thick, it will lead to significant capacity loss; if the thickness of the first coating layer is too thin, it will lead to breakage after a short period of cycling and will not form a complete and uniform coating layer.
[0046] Optionally, the modified graphite material may contain carboxyl or hydroxyl-modified conductive materials, including graphene oxide. Graphite materials coated with graphene oxide, where the graphene oxide is sheet-like and possesses excellent conductivity, can improve the kinetic properties of the first layer material.
[0047] According to the present invention, the mass ratio of the silicon-based material, the carbon material, and the cationic polymer can be (84~97):(2~16):(1~10). In this invention, a suitable mass ratio of silicon-based material, carbon material, and cationic polymer helps to suppress volume expansion. As an example, the mass ratio of silicon-based material, carbon material, and cationic polymer can be any value from 84:2:1, 85:3:3, 86:5:5, 88:6:8, 90:8:9, 95:10:10, and 97:15:10, or any value within the range of any pairwise values mentioned above. In this invention, if the mass ratio of silicon-based material, carbon material, and cationic polymer is too large, it will affect the performance of the silicon-based capacity; if the mass ratio is too small, it will result in poor interfacial bonding and electrode demolding after cycling.
[0048] According to the present invention, the thickness of the second coating layer is 10-50 nm. In this invention, a suitable thickness of the second coating layer helps to improve interface stability. As an example, the thickness of the second coating layer can be any value selected from 10 nm, 20 nm, 30 nm, 40 nm, and 50 nm, or any value within the range formed by any pair of the above values. In this invention, if the thickness of the second coating layer is too thick, it will affect the capacity utilization; if the thickness of the second coating layer is too thin, it will result in a weak bonding effect with other interfaces.
[0049] Optionally, the silicon-based material includes at least one of silicon-carbon materials, silicon-oxygen materials, and nano-silicon.
[0050] Optionally, the silicon-oxygen material includes SiO2. x Where 0.5≤x≤1.5 and / or x=2.
[0051] Optionally, the carbon material includes one-dimensional carbon material or two-dimensional carbon material; or, the carbon material includes zero-dimensional carbon material, and at least one of one-dimensional carbon material and two-dimensional carbon material.
[0052] Optionally, the zero-dimensional carbon material includes graphite particles and / or conductive carbon black.
[0053] Optionally, the one-dimensional carbon material includes carbon nanotubes and / or carbon fibers.
[0054] Optionally, the two-dimensional carbon material includes graphene and / or graphene oxide.
[0055] Optionally, the cationic polymer includes polydiallyldimethylammonium chloride.
[0056] According to the present invention, the mass ratio of the MXene material to the carboxyl- or hydroxyl-modified conductive material can be (90~99):(1~10). In this invention, a suitable mass ratio of MXene material to carboxyl- or hydroxyl-modified conductive material contributes to a uniform conductive network and suppresses cyclic volume expansion. As an example, the mass ratio of MXene material to carboxyl- or hydroxyl-modified conductive material can be any value from 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, and 99:1, or any value within the range of any pair of the above values. In this invention, if the mass ratio of MXene material to carboxyl- or hydroxyl-modified conductive material is too large, it will lead to uneven coating, insufficient conductivity, and, moreover, failure to suppress volume expansion and stabilize the interface.
[0057] According to the present invention, the thickness of the third coating layer is 20 nm to 200 nm. In this invention, a suitable thickness of the third coating layer helps to balance the conductive network structure and the interface structure. As an example, the thickness of the third coating layer can be any value from 20 nm, 30 nm, 40 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, and 200 nm, or any value within the range formed by any pair of the above values. In this invention, if the thickness of the third coating layer is too thick, it will lead to poor interface effects and affect the specific capacity; if the thickness of the third coating layer is too thin, it will lead to insufficient conductivity.
[0058] Optionally, M n+1 X n T x In the material, M is a transition metal element, X is carbon and / or nitrogen, Tx is a surface group, the surface group includes at least one of -O, -OH and -F, and n is an integer from 1 to 3.
[0059] Optionally, the MXene material includes Ti3C2T x .
[0060] Optionally, the modified MXene material may contain carboxyl or hydroxyl-modified conductive materials, including graphene oxide.
[0061] According to the present invention, the first negative electrode active layer may further include a first binder, a first dispersant and a first conductive agent.
[0062] According to the present invention, the mass ratio of the first negative electrode active material, the first binder, the first dispersant, and the first conductive agent can be (95~99):(0.2~2):(0.7~2):(0.1~1). As an example, the mass ratio of the first negative electrode active material, the first binder, the first dispersant, and the first conductive agent can be any value among 95:2:2:1, 96:1:2:1, 97:1:1:1, 98:0.5:1:0.5, and 99:0.2:0.7:0.3, or any value within the range formed by any pair of the above values.
[0063] According to the present invention, the second negative electrode active layer may further include a second binder, a second dispersant, and a second conductive agent.
[0064] According to the present invention, the mass ratio of the second negative electrode active material, the second binder, the second dispersant, and the second conductive agent can be (95~99):(0.2~2):(0.7~2):(0.1~1). As an example, the mass ratio of the second negative electrode active material, the second binder, the second dispersant, and the second conductive agent can be any value among 95:2:2:1, 96:1:2:1, 97:1:1:1, 98:0.5:1:0.5, and 99:0.2:0.7:0.3, or any value within the range formed by any pair of the above values.
[0065] According to the present invention, the third negative electrode active layer may further include a third binder, a third dispersant and a third conductive agent.
[0066] According to the present invention, the mass ratio of the third negative electrode active material, the third binder, the third dispersant, and the third conductive agent can be (95~99):(0.2~2):(0.7~2):(0.1~1). As an example, the mass ratio of the third negative electrode active material, the third binder, the third dispersant, and the third conductive agent can be any value among 95:2:2:1, 96:1:2:1, 97:1:1:1, 98:0.5:1:0.5, and 99:0.2:0.7:0.3, or any value within the range formed by any pair of the above values.
[0067] Optionally, the first adhesive, the second adhesive, and the third adhesive each independently include at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polyacrylate, polyimide, polyamide, polyvinyl alcohol, and polytetrafluoroethylene.
[0068] Optionally, the first dispersant, the second dispersant, and the third dispersant each independently comprise at least one of carboxymethyl cellulose, sodium dodecylbenzene sulfonate, and polyvinylpyrrolidone.
[0069] Optionally, the first conductive agent, the second conductive agent, and the third conductive agent each independently include at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon fibers, and graphene.
[0070] A second aspect of the present invention provides a method for preparing a negative electrode sheet, the method comprising the following steps: S1. A first negative electrode active slurry is coated onto at least one side surface of the current collector along the thickness direction to form a first negative electrode active layer on the current collector. S2. The second negative electrode active slurry is coated on the surface of the first negative electrode active layer away from the current collector to form the second negative electrode active layer on the first negative electrode active layer. S3. Coat the third negative electrode active slurry onto the surface of the second negative electrode active layer away from the first negative electrode active layer to form the third negative electrode active layer on the second negative electrode active layer. The first negative electrode active slurry includes modified graphite material; The second negative electrode active slurry includes modified silicon-based materials; The third negative electrode active slurry includes modified MXene material.
[0071] According to the present invention, in step S1, the coating may further include a first drying and a first rolling; in step S2, the coating may further include a second drying and a second rolling; in step S3, the coating may further include a third drying and a third rolling; or, in steps S1, S2, and S3, after coating is completed, drying and rolling are performed.
[0072] According to the present invention, the preparation steps of the modified graphite material include: mixing a graphite solution and a conductive material solution modified with carboxyl or hydroxyl groups, followed by a fourth drying treatment and a first ball milling treatment.
[0073] According to the present invention, the mass ratio of graphite in the graphite solution to the carboxyl- or hydroxyl-modified conductive material in the conductive material solution can be (500~1000):(5~30). As an example, the mass ratio of graphite in the graphite solution to the carboxyl- or hydroxyl-modified conductive material in the conductive material solution can be any value from 500:5, 600:10, 700:15, 800:20, 900:25, 1000:30, 1000:20, 1000:10, and 1000:5, or any value within the range of any two of the above values.
[0074] According to the present invention, the conductive material solution containing carboxyl or hydroxyl groups may further include a dispersant.
[0075] According to the present invention, the mass ratio of the dispersant to the carboxyl- or hydroxyl-modified conductive material in the solution can be 25:(5~30). As an example, the mass ratio of the dispersant to the carboxyl- or hydroxyl-modified conductive material in the solution can be any value from 25:5, 25:10, 25:15, 25:20, 25:25, and 25:30, or any value within the range of any pair of the above values.
[0076] Optionally, the dispersant includes at least one of polyvinyl alcohol, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.
[0077] In this invention, the dispersant, through steric hindrance, causes the molecular chains in the dispersant to entangle and cover in water, forming a steric hindrance effect that prevents the re-aggregation of conductive materials modified with carboxyl or hydroxyl groups. Polyvinyl alcohol has a better dispersing effect.
[0078] In this invention, the first ball milling process can be dry ball milling; the dry ball milling is carried out under an inert atmosphere, which may include argon; the conditions for dry ball milling include: a rotational speed of 300~500 rpm and a time of 6~12 h. As an example, the rotational speed of the dry ball mill can be any value among 300 rpm, 350 rpm, 400 rpm, 450 rpm, and 500 rpm, or any value within the range formed by any two of the above values; the dry ball milling time can be any value among 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, and 12 h, or any value within the range formed by any two of the above values.
[0079] In this invention, the uniformity of the coating layer and the bonding force with the matrix in the modified graphite material are ensured by the fourth drying treatment and the first ball milling treatment.
[0080] According to the present invention, the solvent in the graphite solution may include alcohols; optionally, the alcohols may include n-hexanol; optionally, the ratio of graphite to solvent in the graphite solution is (500~100) g: 102 mL.
[0081] According to the present invention, the solvent for the conductive material solution containing carboxyl or hydroxyl groups may include water.
[0082] According to the present invention, the preparation steps of the modified silicon-based material may include: S21. The silicon-based material and carbon material solution are mixed, dispersed, and first separated to obtain a first precipitate; the first precipitate is then carbonized to obtain an intermediate. S22. The solution containing the intermediate and the cationic polymer suspension are mixed, dispersed, and then separated to obtain a second precipitate; S23. The second precipitate is subjected to a fifth drying treatment and an annealing treatment in sequence.
[0083] According to the present invention, in step S21, the mass ratio of the silicon-based material to the carbon material in the carbon material solution can be 50:(1~8). As an example, the mass ratio of the silicon-based material to the carbon material in the carbon material solution is any value among 50:1, 50:2, 50:3, 50:4, 50:5, 50:6, 50:7, and 50:8, or any value within the range of any pair of the above values.
[0084] According to the present invention, in step S21, the solvent in the carbon material solution may include an alcohol solvent, and optionally, the alcohol solvent includes ethanol.
[0085] According to the present invention, in step S22, the volume ratio of the solution containing the intermediate to the cationic polymer suspension can be from 2:1 to 10:1. As an example, the volume ratio of the solution containing the intermediate to the cationic polymer suspension can be any value from 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1, or any value within the range formed by any two of the above values.
[0086] According to the present invention, in step S22, the concentration of the intermediate in the solution containing the intermediate can be 1 to 10 mg / mL. As an example, the concentration of the intermediate can be any value selected from 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, and 10 mg / mL, or any value within the range formed by any pair of the above values.
[0087] According to the present invention, in step S22, the solvent in the solution containing the intermediate may include water.
[0088] According to the present invention, in step S22, the concentration of the cationic polymer in the cationic polymer suspension can be 0.1~1 mg / mL. As an example, the concentration of the cationic polymer can be any value selected from 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, and 1 mg / mL, or any value within the range formed by any pair of the above values.
[0089] According to the present invention, in step S22, the solvent in the cationic polymer suspension may include water.
[0090] According to the present invention, in step S21, the first separation can be vacuum filtration; optionally, the carbonization treatment is carried out under an inert atmosphere, the inert atmosphere including nitrogen; the conditions of the carbonization treatment include: a temperature of 300~500℃ and a time of 1~4h. As an example, the temperature of the carbonization treatment can be any value among 300℃, 350℃, 400℃, 450℃ and 500℃ or any value within the range formed by any two of the above values, and the time of the carbonization treatment can be any value among 1h, 2h, 3h and 4h or any value within the range formed by any two of the above values.
[0091] According to the present invention, in step S23, the fifth drying process can be a first freeze-drying, and the conditions for the first freeze-drying can include: a temperature of -40 to -80°C and a time of 12 to 36 hours. As an example, the temperature of the first freeze-drying can be any value among -40°C, -50°C, -60°C, -70°C, and -80°C, or any value within the range formed by any two of the above values. The time of the first freeze-drying can be any value among 12 hours, 15 hours, 20 hours, 24 hours, 25 hours, 30 hours, 35 hours, and 36 hours, or any value within the range formed by any two of the above values.
[0092] According to the present invention, in step S23, the annealing conditions may include: a temperature of 400°C and a time of 5 to 12 hours. As an example, the annealing time may be any value among 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours, or any value within the range of any two of the above values.
[0093] According to the present invention, the preparation steps of the modified MXene material may include: mixing a conductive material dispersion containing carboxyl or hydroxyl groups and an MXene dispersion, and then sequentially performing a second ball milling treatment, a standing treatment, and a sixth drying treatment.
[0094] According to the present invention, the volume ratio of the carboxyl- or hydroxyl-modified conductive material dispersion to the MXene dispersion can be 1:2 to 1:10. As an example, the volume ratio of the carboxyl- or hydroxyl-modified conductive material dispersion to the MXene dispersion can be any value from 1:2, 5, 1:6, 1:7, 1:8, 1:9, and 1:10, or any value within the range of any two of the above values.
[0095] According to the present invention, in the dispersion of the carboxyl or hydroxyl-modified conductive material, the concentration of the carboxyl or hydroxyl-modified conductive material can be 0.1 to 0.4 mg / mL. As an example, the concentration of the carboxyl or hydroxyl-modified conductive material can be any value selected from 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, and 0.4 mg / mL, or any value within the range formed by any pair of the above values.
[0096] According to the present invention, the solvent in the dispersion of conductive materials modified with carboxyl or hydroxyl groups may include water.
[0097] According to the present invention, the concentration of MXene in the MXene dispersion can be 1 to 4 mg / mL. As an example, the concentration of MXene can be any value among 1 mg / mL, 2 mg / mL, 3 mg / mL and 4 mg / mL or any value within the range of any two of the above values.
[0098] According to the present invention, the solvent in the MXene dispersion may include water.
[0099] According to the present invention, the second ball milling process can be wet ball milling, and the conditions for wet ball milling may include: a rotational speed of 400-600 rpm and a time of 20-60 min. As an example, the rotational speed of the wet ball milling can be any value among 400 rpm, 450 rpm, 500 rpm, 550 rpm, and 600 rpm, or any value within the range formed by any two of the above values; the time of the wet ball milling can be any value among 20 min, 30 min, 40 min, 50 min, and 60 min, or any value within the range formed by any two of the above values.
[0100] According to the present invention, the conditions for the settling treatment may include: a temperature of 15~35°C and a time of 1.5~2.5h. As an example, the settling temperature may be any value among 15°C, 20°C, 25°C, 30°C, and 35°C, or any value within the range formed by any two of the above values; the settling time may be any value among 1.5h, 2h, and 2.5h, or any value within the range formed by any two of the above values.
[0101] According to the present invention, the sixth drying process can be a second freeze-drying, and the conditions for the second freeze-drying can include: a temperature of -40 to -80°C and a time of 18 to 30 hours. As an example, the temperature for the second freeze-drying can be any value among -40°C, -50°C, -60°C, -70°C, and -80°C, or any value within the range formed by any two of the above values; the time for the second freeze-drying can be any value among 18 hours, 20 hours, 24 hours, 25 hours, and 30 hours, or any value within the range formed by any two of the above values.
[0102] A third aspect of the present invention provides a battery comprising a negative electrode, wherein the negative electrode comprises the negative electrode described above or a negative electrode prepared according to the preparation method described above.
[0103] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0104] Preparation Example 1 The preparation of modified graphite materials includes the following steps: (1) Add 500g of artificial graphite powder to 102mL of n-hexanol and stir at 300r / min for 10h to obtain a graphite solution.
[0105] (2) Dissolve 5g of graphene oxide and 25g of polyvinyl alcohol in deionized water and stir to obtain a graphene oxide solution.
[0106] (3) Mix the graphite solution with the graphene oxide solution and stir at room temperature for 8 hours to obtain a suspension; dry the suspension in an oven at 85°C, sieve the dried product, and then dry ball mill it at 400 rpm for 8 hours under an Ar protective atmosphere to obtain the modified graphite material.
[0107] Preparation Example 2 The preparation of modified silicon-based materials includes the following steps: (1) Weigh 50g of carbon nanotubes and place them in a 1000mL beaker. Add 300mL of ethanol to the beaker and stir magnetically to disperse the carbon nanotubes in the ethanol to obtain a carbon nanotube solution. Add 1g of silicon dioxide to the carbon nanotube solution, add 100mL of ethanol to dilute, sonicate, stir and mix for 30min, and then perform vacuum filtration step by step. After filtration, dry the obtained product at 80℃, and then carbonize the dried product at 400℃ for 2h under a nitrogen atmosphere to obtain an intermediate.
[0108] (2) Mix 100 mL of polydiallyl dimethyl ammonium chloride (PDDA) suspension with a concentration of 0.5 mg / mL and 200 mL of intermediate solution with a concentration of 1 mg / mL, stir, disperse and separate to obtain precipitate.
[0109] (3) The precipitate was freeze-dried at -40℃ for 12h. After the freeze-drying was completed, the product was annealed at 400℃ for 10h to obtain the modified silicon-based material.
[0110] Preparation Example 3 The preparation of modified MXene materials includes the following steps: (1) Mix 1g of lithium fluoride (LiF) with 9mol / L hydrochloric acid (HCl) and stir for 20min. Then place it in a 30℃ water bath and add 1g of titanium aluminum carbide (Ti3AlC2, MAX phase) in batches for magnetic stirring and etching for 36h. After the water bath reaction is completed, the product is centrifuged and washed until pH≈6. Then, it is sonicated in an ice bath under argon atmosphere for 1h, centrifuged for 0.5h, and freeze-dried for 36h to obtain Ti3C2T x .
[0111] (2) 20 mL of 0.2 mg / mL aqueous dispersion of graphene oxide and 40 mL of 2 mg / mL Ti3C2T were respectively added to the aqueous dispersion of graphene oxide. x The aqueous dispersion was sonicated for 40 min and then mixed with the other two materials. The mixture was then wet-milled at 400 rpm / min for 3 h at room temperature. After wet-milling, the mixture was allowed to stand for 2 h and then freeze-dried at -40℃ for 24 h to obtain the modified MXene material.
[0112] Example 1 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.08 g / cm. 2 The first coating 20.
[0113] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30.
[0114] (3) The modified MXene material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a third slurry with a solid content of 50 wt%; wherein the mass ratio of the modified MXene material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the third slurry is 96.5:1:1.5:1; the third slurry is coated on the second coating layer 20, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0115] Example 2 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein, the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.04 g / cm. 2 The first coating 20.
[0116] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.08 g / cm³. 2 The second coating 30.
[0117] (3) The modified MXene material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a third slurry with a solid content of 50 wt%; wherein the mass ratio of the modified MXene material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the third slurry is 96.5:1:1.5:1; the third slurry is coated on the second coating layer 20, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0118] Example 3 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein, the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.04 g / cm. 2 The first coating 20.
[0119] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30.
[0120] (3) The modified MXene material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a third slurry with a solid content of 50 wt%; wherein the mass ratio of the modified MXene material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the third slurry is 96.5:1:1.5:1; the third slurry is coated on the second coating layer 20, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.08 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0121] Comparative Example 1 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.08 g / cm. 2 The first coating 20.
[0122] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30 is then applied to obtain the negative electrode.
[0123] Comparative Example 2 The preparation of the negative electrode includes the following steps: (1) Artificial graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein, the mass ratio of artificial graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.08 g / cm. 2 The first coating 20.
[0124] (2) A second slurry with a solid content of 50 wt% is obtained by mixing silicon dioxide (silicon-based material), styrene-butadiene rubber (SBR) (binder), sodium carboxymethyl cellulose (CMC) (dispersant), carbon black (conductive agent), and water. The mass ratio of silicon dioxide, styrene-butadiene rubber, sodium carboxymethyl cellulose, and carbon black in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30.
[0125] (3) MXene material Ti3C2T x A third slurry with a solid content of 50 wt% is obtained by mixing styrene-butadiene rubber (SBR) as a binder, sodium carboxymethyl cellulose (CMC) as a dispersant, carbon black as a conductive agent, and water; wherein, the MXene material Ti3C2T in the third slurry... xThe mass ratio of the binder (styrene-butadiene rubber), dispersant (sodium carboxymethyl cellulose), and conductive agent (carbon black) is 96.5:1:1.5:1. The third slurry is coated onto the second coating layer 20, then dried at 80°C, and subsequently rolled. The compacted density after rolling is 0.2 g / cc, forming a layer with a thickness of 0.025 mm and an areal density of 0.04 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0126] Comparative Example 3 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.08 g / cm. 2 The first coating 20.
[0127] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30.
[0128] The preparation method of the modified silicon-based material includes the following steps: A solution of polydiallyl dimethyl ammonium chloride (PDDA) with a concentration of 0.5 mg / mL and a silicon dioxide solution with a concentration of 1 mg / mL were stirred, dispersed and separated at a volume ratio of 1:2 to obtain a precipitate.
[0129] The precipitate was freeze-dried at -40℃ for 12 hours. After freeze-drying, the resulting product was annealed at 400℃ for 10 hours to obtain the modified silicon-based material.
[0130] (3) The modified MXene material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a third slurry with a solid content of 50 wt%; wherein the mass ratio of the modified MXene material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the third slurry is 96.5:1:1.5:1; the third slurry is coated on the second coating layer 20, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0131] Comparative Example 4 The preparation of the negative electrode includes the following steps: (1) Modified graphite material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a first slurry with a solid content of 50 wt%; wherein the mass ratio of modified graphite material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the first slurry is 96.5:1:1.5:1; the first slurry is coated on both sides of a current collector copper foil 10 with a thickness of 8 μm along the thickness direction, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, so as to form a current collector copper foil 10 with a thickness of 0.05 mm and an areal density of 0.08 g / cm. 2 The first coating 20.
[0132] (2) A second slurry with a solid content of 50 wt% is obtained by mixing modified silicon-based material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water. The mass ratio of modified silicon-based material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the second slurry is 96.5:1:1.5:1. The second slurry is coated on the first coating layer 20, dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The second coating 30.
[0133] The preparation method of the modified silicon-based material includes the following steps: Weigh 500g of carbon nanotubes and place them in a 1000mL beaker. Add 300ml of ethanol to the beaker and stir magnetically to disperse the carbon nanotubes in the ethanol to obtain a carbon nanotube solution. Add the carbon nanotube aqueous solution to the beaker using a pipette at a ratio of silicon dioxide to carbon nanotubes of 50:1. Dilute with 100ml of ethanol, sonicate, and then add to the silicon-carbon-ethanol system. Stir and mix for 30min, and then perform stepwise vacuum filtration. After filtration, dry the obtained product at 80℃, and then carbonize the dried product at 400℃ for 2h under a nitrogen atmosphere to obtain the modified silicon-based material.
[0134] (3) The modified MXene material, styrene-butadiene rubber (SBR) binder, sodium carboxymethyl cellulose (CMC) dispersant, carbon black conductive agent, and water are mixed to obtain a third slurry with a solid content of 50 wt%; wherein the mass ratio of the modified MXene material, styrene-butadiene rubber binder, sodium carboxymethyl cellulose dispersant, and carbon black conductive agent in the third slurry is 96.5:1:1.5:1; the third slurry is coated on the second coating layer 20, then dried at 80°C, and then rolled. The compaction density after rolling is 0.2 g / cc, forming a thickness of 0.025 mm and a surface density of 0.04 g / cm³. 2 The third coating 40 is then applied to obtain the negative electrode.
[0135] Performance testing 1. Battery manufacturing (1) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate (LFP), binder polyvinylidene fluoride (PVDF) and conductive agent conductive carbon black are mixed in a mass ratio of 97:1.5:1.5 and dispersed to obtain a mixture. Then, the solvent N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 75wt%. The positive electrode slurry is coated on an aluminum foil with a thickness of 10μm, dried, cold pressed, and then die-cut to obtain a positive electrode sheet.
[0136] (2) Battery Assembly: The positive electrode sheet and the negative electrode sheet from the examples and comparative examples are dried and cold-pressed. The treated positive electrode sheet and the separator (polypropylene separator) are stacked in sequence with the treated negative electrode sheet from the examples and comparative examples, respectively, and a bare cell is obtained by winding. Aluminum tabs and copper-plated nickel tabs are connected respectively. The bare cell is placed in a high-temperature vacuum baking at 85°C for 24 hours and then sealed with aluminum-plastic film. The electrolyte is a lithium hexafluorophosphate electrolyte containing 1M, and the solvent is a mixed solvent of ethylene carbonate / dimethyl carbonate / 1,2-propylene glycol carbonate in a 1:1:1 (volume ratio). After sealing, sufficient electrolyte is injected, and then the battery is formed, aged, and sealed again to obtain a lithium-ion battery.
[0137] 2. Performance Testing This experiment used a pouch battery system to test various electrochemical performance parameters. The Wuhan Landian CT200A battery testing system was used to test the constant current charge-discharge cycle performance, rate performance, and charge-discharge curves. The voltage scan range was 2~3.65V.
[0138] (1) Negative electrode design capacity: refers to the design of the negative electrode material, that is, the amount of charge that can be stored per unit mass (usually in grams) in the battery negative electrode material (usually in milliampere-hours, mAh).
[0139] (2) The method for testing the maximum continuous charging rate is as follows: ① Let the battery stand at room temperature (25℃) for 4 hours; ③ Charge the battery at a constant current and constant voltage of nC to 3.65V, and cut off at 0.05C, n=1,1.5,2,2.5,3,3.5,4…; ④ Let the battery stand at room temperature for 2 hours; Repeat the above steps to complete all different charging rates. After charging at the specified rate, perform electrical disassembly to confirm the lithium plating situation. If lithium plating is observed on the electrode of the battery group after full charging, it indicates that the battery produces lithium plating at this rate. If no lithium plating is produced on the electrode interface of the previous test rate, then the maximum continuous charging rate is this rate.
[0140] (3) The method for testing the 0-100% SOC fast charging time is as follows: ① At 25℃, first charge at a 4C rate to 3.65V, then charge at a 3.6C rate to 3.65V, and so on, charging at different rates (4C, 3.6C, 3.2C, 2.8C, 2, 6C, 2.2C, 1.8C, 1.6C, 1.2C, 0.8C, 0.33C) until finally charging at 0.33C to 100% SOC. Record the time to charge to 3.65V at each rate, and sum up the times to get the 0-100% fast charging time. (4) The method for testing low-temperature charging capability is as follows: ① Voltage range: 2.5V~3.65V, temperature: -20℃; ② Let stand for 120min; ③ Constant current charging: charge with IC at a constant current to the upper limit voltage until the charging cutoff voltage of 3.65V is reached; ④ Let stand for 30min; ⑤ Discharge at 0.3C to the lower limit voltage; ⑥ Repeat steps ②~⑤ 10 times; ⑦ Let stand for 30min; change the current, where I=0.1C, 0.15C, 0.2C, 0.25C, 0.3C, 0.4C, 0.5C… Repeat steps ①-⑦, and record the lithium deposition at the negative electrode interface of each battery at different rates. If there is lithium deposition at the negative electrode interface after 10 cycles at this rate, and no lithium deposition occurs at the interface under the previous rate test, then the previous rate is the maximum acceptable charging current at low temperature -20℃; (5) 500-cycle full-charge thickness test of negative electrode sheet: First, record the original thickness of the negative electrode sheet, denoted as L1. Place the battery in a normal temperature environment (25℃±2). Charge the battery at 1C constant current to 3.65V, let it stand for 30 minutes, and discharge it at constant current to 2.5V. This process is considered one cycle. Record 500 cycles. Then, fully charge the battery and disassemble it. Use a micrometer to measure the thickness of the negative electrode sheet at full charge, denoted as L2. Change rate = (L2-LI) / (L1-foil thickness).
[0141] As shown in Table 1, the specific capacity design of the negative electrode is as follows: In Example 2, the proportion of silicon-oxygen is relatively high, and silicon-oxygen itself has a high capacity, so the capacity design is relatively high. In Example 3, the capacity decreases significantly mainly due to the high content of MXene material. In the comparative example, the capacity is slightly higher than that of Example 1 because there is no third MXene coating. The other comparative examples are basically the same as those of Example 1.
[0142] Maximum continuous charging rate / fast charging time: Combining Examples 1-3, it was found that Example 1 was the best. Because Example 3 has more MXene material than Example 2, the MXene coated with graphene oxide solved the self-stacking problem and widened the interlayer spacing, thus enhancing the fast charging capability. Compared with Comparative Example 1, which has no MXene, the fast charging capability decreased. Comparative Example 2 was the worst because of poor kinetics, and none of the coating materials underwent surface modification.
[0143] Low-temperature charging capability: At low temperatures, Examples 1-3 and Comparative Example 4 exhibited improved charging capability due to the rapid temperature rise caused by the construction of a three-dimensional conductive network and the excellent electrical and thermal conductivity of graphene, carbon nanotubes, and the Mxene material in the third layer. Comparative Example 2, although coated with three layers, lacked a surface coating with good conductivity, resulting in poor kinetics at low temperatures. Comparative Examples 1 and 3, while possessing some conductivity, did not form a three-dimensional conductive network.
[0144] Negative electrode thickness change rate at full discharge: Comparing Examples 1-3, Example 1 was found to be the optimal one, exhibiting the smallest negative electrode thickness change rate. This is attributed to the reasonable formulation and the strong bending strength and large interlayer spacing of MXene coated with graphene oxide, which can accommodate the volume expansion of the second layer of silicon oxide during charging and discharging. Furthermore, the downward stress expansion is released by the first layer. Compared to Comparative Example 1, without the third layer of MXene possessing tensile and bending strength, the thickness change reached 22.1%. Therefore, placing the silicon layer as the second layer can improve capacity and lithium intercalation potential while suppressing expansion and protecting the electrode structure. In Examples 1 and Comparative Example 3, the enhanced bonding force between PDDA and the surface of graphene oxide plays a crucial role in improving interface stability.
[0145] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes: a negative electrode current collector, a first negative electrode active layer disposed on at least one side surface of the negative electrode current collector along the thickness direction, a second negative electrode active layer disposed on one side surface of the first negative electrode active layer away from the negative electrode current collector, and a third negative electrode active layer disposed on one side surface of the second negative electrode active layer away from the first negative electrode active layer. The first negative electrode active layer includes a first negative electrode active material, which includes a modified graphite material; the modified graphite material includes graphite and a first coating layer covering the surface of the graphite, the first coating layer including graphene oxide. The second negative electrode active layer includes a second negative electrode active material, which includes a modified silicon-based material; the modified silicon-based material includes a silicon-based material and a second coating layer covering the surface of the silicon-based material, the second coating layer including a carbon material and a cationic polymer; The third negative electrode active layer includes a third negative electrode active material, which includes a modified MXene material. The modified MXene material includes an MXene material and a third coating layer covering the surface of the MXene material. The third coating layer includes graphene oxide. The cationic polymer includes polydiallyldimethylammonium chloride.
2. The negative electrode sheet according to claim 1, characterized in that, The negative electrode includes one or more of the following features (1) to (4): (1) The areal density ratio of the first negative electrode active layer, the second negative electrode active layer and the third negative electrode active layer is (1~3):(1~3):(1~3); (2) The areal density of the first negative electrode active layer is 0.01~0.12 g / cm³. 2 ; (3) The areal density of the second negative electrode active layer is 0.01~0.12 g / cm³. 2 ; (4) The areal density of the third negative electrode active layer is 0.01~0.12 g / cm³. 2 .
3. The negative electrode sheet according to claim 1, characterized in that, The negative electrode includes one or more of the following features (1) to (4): (1) The thickness ratio of the first negative electrode active layer, the second negative electrode active layer and the third negative electrode active layer is (1.25~3.35):(1~2):(1~2); (2) The thickness of the first negative electrode active layer is 0.044~0.067 mm; (3) The thickness of the second negative electrode active layer is 0.02~0.040 mm; (4) The thickness of the third negative electrode active layer is 0.02~0.040 mm.
4. The negative electrode sheet according to claim 1, characterized in that, The modified graphite material includes one or more of the following features (1) to (2): (1) The mass ratio of the graphite to the graphene oxide is (94~99):(1~6); (2) The thickness of the first coating layer is 20~80nm.
5. The negative electrode sheet according to claim 1, characterized in that, The modified silicon-based material includes one or more of the following features (1) to (4): (1) The mass ratio of the silicon-based material, the carbon material and the cationic polymer is (84~97):(2~16):(1~10); (2) The thickness of the second coating layer is 10~50nm; (3) The silicon-based material includes at least one of silicon-carbon materials, silicon-oxygen materials, and nano-silicon; The silicon-oxygen material includes SiO₂. x Where 0.5 ≤ x ≤ 1.5 and / or x = 2; (4) The carbon material includes one-dimensional carbon material or two-dimensional carbon material; or, the carbon material includes zero-dimensional carbon material, and at least one of one-dimensional carbon material and two-dimensional carbon material; The zero-dimensional carbon material includes graphite particles and / or conductive carbon black; the one-dimensional carbon material includes carbon nanotubes and / or carbon fibers; and the two-dimensional carbon material includes graphene and / or graphene oxide.
6. The negative electrode sheet according to claim 1, characterized in that, The modified MXene material includes one or more of the following features (1) to (3): (1) The mass ratio of the MXene material to the graphene oxide is (90~99):(1~10); (2) The thickness of the third coating layer is 20nm~200nm; (3) The MXene material includes Ti3C2T x .
7. The negative electrode sheet according to claim 1, characterized in that, The negative electrode includes one or more of the following features (1) to (3): (1) The first negative electrode active layer further includes a first binder, a first dispersant, and a first conductive agent; The mass ratio of the first negative electrode active material, the first binder, the first dispersant, and the first conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1). (2) The second negative electrode active layer also includes a second binder, a second dispersant, and a second conductive agent; The mass ratio of the second negative electrode active material, the second binder, the second dispersant, and the second conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1). (3) The third negative electrode active layer further includes a third binder, a third dispersant, and a third conductive agent; The mass ratio of the third negative electrode active material, the third binder, the third dispersant and the third conductive agent is (95~99):(0.2~2):(0.7~2):(0.1~1).
8. The negative electrode sheet according to claim 7, characterized in that, The negative electrode includes one or more of the following features (1) to (3): (1) The first adhesive, the second adhesive and the third adhesive each independently include at least one of styrene-butadiene rubber, polyvinylidene fluoride, polyacrylic acid, polyacrylate, polyimide, polyamide, polyvinyl alcohol and polytetrafluoroethylene; (2) The first dispersant, the second dispersant and the third dispersant each independently comprise at least one of carboxymethyl cellulose, sodium dodecylbenzene sulfonate and polyvinylpyrrolidone; (3) The first conductive agent, the second conductive agent and the third conductive agent each independently include at least one of conductive carbon black, conductive graphite, carbon nanotubes, carbon fibers and graphene.
9. A method for preparing the negative electrode sheet according to any one of claims 1 to 8, characterized in that, The preparation method includes the following steps: S1. A first negative electrode active slurry is coated onto at least one side surface of the current collector along the thickness direction to form a first negative electrode active layer on the current collector. S2. The second negative electrode active slurry is coated on the surface of the first negative electrode active layer away from the current collector to form the second negative electrode active layer on the first negative electrode active layer. S3. Coat the third negative electrode active slurry onto the surface of the second negative electrode active layer away from the first negative electrode active layer to form the third negative electrode active layer on the second negative electrode active layer. The first negative electrode active slurry includes modified graphite material; The second negative electrode active slurry includes modified silicon-based materials; The third negative electrode active slurry includes modified MXene material.
10. A battery, characterized in that, The battery includes a negative electrode sheet, wherein the negative electrode sheet includes the negative electrode sheet according to any one of claims 1 to 8 or the negative electrode sheet prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Negative plate and lithium ion battery comprising same
CN114050234A
Negative plate and battery
CN115377350A